Hubungan Kadar Glukosa Darah dengan Skor Fungsi Kognitif pada Pasien Stroke Iskemik di RSUD Dr. Moewardi Surakarta - Maria Goretti Novianty Hutauruk; Oemar Sri Hartanto; Bhisma Murti; Agus Soedomo (Nexus Kedokteran Klinik, 2012)
Objective: The aim of the study is to determain the relation between blood glucose level and cognitive function score in stroke ischemic patient at RSUD Dr. Moewardi. Background: . An ischemic stroke is death of an area of brain tissue (cerebral infarction) resulting from an inadequate supply of blood and oxygen to the brain due to blockage of an artery. Cognitive impairmentsthat may be experiencedafter theoccurrenceof strokeincludedifficulty concentratingforthe amountof time, organization,forgetfulnessand being easilyconfused. The state of hyperglycemia is common in the acute phase of stroke caused by stress and an increase in serum catecholamines. This study aimed to proof that their blood glucose levels rise will increase infarct size, decreased cognitive function and clinical output effects are worse, especially in non-hemorrhagic stroke Methods: This analytic study was analytic observational with cross-sectional approach. A sample of 50 study subjects was selected by random sampling from outpatients with stroke ischemic visiting the Neurology Clinics, RSUD Dr. Moewardi Surakarta. The data were collected by interview using a set of questionnaire. The data was analyszed using multiple linear regression model on SPSS version 17 for Windows. Results: There is a negative significant association between blood glucose level and Patients stroke ischemic with blood glucose level ?145mg/dL has MMSE score 5,39 point lower than blood glucose level <145mg/dL ( b= -5,39 ; CI 95% -6,98 sampai -3,81; p<0,001). This estimate has controlled for the effects of confounding variables such as level of education and age. Conclusion: There is a statistically significant association between blood glucose level and cognitive function score in stroke ischemic patient. This conclusion is drawn after controlling for the effects of confounding factors such as level of education and age. Keywords: Stroke ischemic,blood glucose level, cognitive functional score.